Changes of the Posterior Airway Space Following Orthognathic Surgery in Class III - Setoudeh Maram, Shahin; Masoumi, Sara; Momeni Danaei, Shahla; Zamiri, Barbod (Journal of Dental School, 2019)
Objective: Adaptation of the pharyngeal airway space does occur after different surgical strategies of class III patients including mandibular setback, maxillary advancement and bimaxillary surgery. The aim of this study is to conduct a detailed cephalometric evaluation of the alterations taking place in the morphology of the pharyngeal airway space after treatment of class III skeletal deformity via different surgical procedures (i.e. mandibular setback, maxillary advancement, bimaxillary surgery) in both males and females. Methods: This study is a before-after cross sectional retrospective research. One hundred and twenty consecutive patients who were diagnosed as having skeletal class III deformity. All patients included in this study were adults who had completed their growth and had cephalograms within a month prior to operation (T1) and 1 month to 9 months post-surgery (T2) taken in the natural head position. Patients were divided according to the type of surgery undertaken in three groups: group 1 (bimaxillary), group 2 (mandibular setback) and group 3 (maxillary advancement) surgeries. Posterior airway size was evaluated at both T1 and T2 in each group. The results were compared by paired t and one-way ANOVA tests. Results: Airway size decreased significantly in group 1 and 2 (p<0.05) but increased in group 3(p<0.05). Conclusion: Airway dimension and morphology as well as head and neck posture changed significantly in different surgical treatments of class III deformity.